RANCANGAN INFORMASI AKUNTANSI : TRANSAKSI BERBASIS ONLINE PRODUK UNGGULAN UMKM SONGKET RIAU SEBAGAI PENINGKATAN EKONOMI SONGKET MELAYU DALAM KONTEKS HASANAH KEARIFAN BUDAYA RIAU - Enny Susilowati; Emrinaldi Nur DP (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
The research examines the marketing system and a simple accounting bookkeeping transaction-based online web 2.0. The system Web 2.0 is used as trend center of the SMEs RiauMelayu songket to promote their products as well as typical local wisdom elevates the Melayu Songket. The success of SystemWeb 2.0 is themodel ofweb-based marketing system with simple accounting bookkeeping can run effectively and efficiently, which is built with each character SMEs Riau Melayu songket. The purpose ofthis systemof Web 2.0 is good customer in teraction to the system.Consumers SMEs are willing to share knowledge songket product and satisfied with the service of the products such as ease of payment because it supported a good simple accounting bookkeeping. Some of the SMEs to transform knowledge into innovative products or services. This research use sample consisted of 45 people from SMEs Riau who act as the owner, co-owner, accounting, labor, marketing, songket weavers scattered in the RIAU area. The data are taken with the collecting of data into observation, interviews and questionnaires central. Selection of samples by using purposive sampling.The method is a descriptive to explore Marketing Model and application of financial records Riau SMEs based on systemweb 2.0. The result of the research Indicated integrated system that combines all the elements of art and Riau Melayu culture and its financial records in a web site that is easily accessible web bases or very useful. This is not only aimed at the improvement of the economy craftsmen and merchants SMEs Riau Melayu batik and songket, but also it’s means of promotion, enhancement obedient bookkeeping, as well as increased regional revenue for the province of Riau